AN INVESTIGATION OF FAITHFULNESS MODEL FOR BUDDHIST IN SCANDINAVIA COUNTRIES - Nyanaviro (Tanodkaew), PhrapaladKlanarong; Dhanapañño, Phramaha Sombat; Srivichai, Suddhipong; Chirakulo (Jongsakulsiri), Phramaha Padet (Journal of Educational Review Faculty of Education in MCU, 2021)
The purpose of this research article was to investigate a faithfulness model for Buddhists in Scandinavia countries. Mixed methods research was designed, and there were three steps in this research method. Step 1: Study the current situation and problems of Buddhist in Scandinavia countries by interviewing 6 key informants using purposive sampling. Step 2: Develop a model by focus group discussion of 17 experts using purposive sampling. Step 3 investigate and propose a faithfulness model for Buddhists in Scandinavia countries from 300 Buddhists in Scandinavia countries. Data were analyzed by statistical analysis consisted of frequency, percentage, mean and standard deviation. Results of the research found that the investigation of faithfulness model for Buddhist in Scandinavia countries consisted of 3 parts which were introduction, the model, and the implementation process. The overall investigation was at a high level. When considering each aspect, it was at a high level in all aspects, namely feasibility, suitability, usefulness and correctness.